Mapping the Interests, Talents and Character Profiles of Pancasila Students in High School Students - Nisa Ariantini; Kusumawati (Bisma The Journal of Counseling, 2023)
The Pancasila student profile is the character and competency Indonesian students must have when learning and entering society. This research aims to determine the description of student character based on the Pancasila student profile. This research is classified as a descriptive research type using the library research method. This research used reading methods, literature notes, and different components. Research studies conduct reading activities, then filter and reflect on related theories. Furthermore, this research also uses the site method (website visit). Library data collection techniques are carried out through references and written information. Research data analysis is carried out after data collection using the classification method to provide group identification (name) for the research variables. The results of the research analysis show that the values contained in the Pancasila student profile are religion, honesty, tolerance, discipline, hard work, creativity, independence, democracy, curiosity, national spirit, love of the country, respect for achievement, friendly/ communicative, loves peace, likes reading, cares about the environment, cares about social affairs and responsibility. This education emphasizes character education, which instills character values in students, which contains elements of knowledge, individual awareness, and determination, as well as the will and action to implement values, both towards God Almighty, oneself, fellow human beings, the environment, as well as the nation, which is an obligation for all parties.